Comparison of postoperative costs of two surgical techniques for hallux valgus (Kramer vs. scarf). Issue 1 (March 2015) - Poggio, Daniel; Melo, Rodrigo; Botello, Julio; Polo, Carlos; Retana, Pablo Fernández de; Asunción, Jordi
Highlights We compare the care burden and economic cost of two surgical approaches to hallux valgus correction. Care burden was assessed by the number of visits each patient required and the complications. The follow-up and costs of each were assessed and compared independently. Kramer osteotomy presented significantly higher care burdens, complication rates and associated costs during the first year of follow-up.